Reversing drug resistance of soft tumor-repopulating cells by tumor cell-derived chemotherapeutic microparticles - Ma, Jingwei (Cell Res, 2016)
Developing novel approaches to reverse the drug resistance of tumor-repopulating cells (TRCs) or stem cell-like cancer cells is an urgent clinical need to improve outcomes of cancer patients. Here we show an innovative approach that reverses drug resistance of TRCs using tumor cell-derived microparticles (T-MPs) containing anti-tumor drugs. TRCs, by virtue of being more deformable than differentiated cancer cells, preferentially take up T-MPs that release anti-tumor drugs after entering cells, which in turn lead to death of TRCs. The underlying mechanisms include interfering with drug efflux and promoting nuclear entry of the drugs. Our findings demonstrate the importance of tumor cell softness in uptake of T-MPs and effectiveness of a novel approach in reversing drug resistance of TRCs with promising clinical applications.